2009
DOI: 10.1111/j.1472-765x.2009.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

RecAgene sequence and Multilocus Sequence Typing for species-level resolution ofBurkholderia cepaciacomplex isolates

Abstract: Aim:  To identify, by means of recA sequencing and multilocus sequence typing (MLST), Burkholderia cepacia complex (BCC) isolates of environmental and clinical origin, which failed to be identified by recA RFLP and species‐specific PCR. Methods and Results:  By using recA sequence‐based identification, 17 out of 26 BCC isolates were resolved at the level of species and lineage (ten Burkholderia cenocepacia IIIB, two Burkholderia arboris and five Burkholderia lata). By using MLST method, 24 BCC isolates were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Although several protocols have been developed to discriminate individual species (4,8,10), multilocus sequence typing (MLST) has proven to be the only method which has kept pace with the increasing complexity of BCC species. By sequence analysis of seven housekeeping genes, MLST enables unequivocal identification of all established BCC species and also has the advantage of being able to define novel BCC groups (1,3,7). In addition, it can serve as a highly standardized genotyping method that provides robust information on strain type, by defining a sequence type (ST).…”
mentioning
confidence: 99%
“…Although several protocols have been developed to discriminate individual species (4,8,10), multilocus sequence typing (MLST) has proven to be the only method which has kept pace with the increasing complexity of BCC species. By sequence analysis of seven housekeeping genes, MLST enables unequivocal identification of all established BCC species and also has the advantage of being able to define novel BCC groups (1,3,7). In addition, it can serve as a highly standardized genotyping method that provides robust information on strain type, by defining a sequence type (ST).…”
mentioning
confidence: 99%
“…Amplification of recA with primers BCR1 and BCR2 can be used as an initial means of placing an isolate within the Bcc; after successful amplification of recA, RFLP with HaeIII and MnlI may be used to place the isolate within a specific genomovar or recA group [26,27,39,40]. Recently, it was found that MLST could identify Bcc isolates which were not identified by means of recA RFLP and species-specific PCR [41,42]. Detection of cblA, the cable pilus gene [43], and a novel marker, ecfB [44], are new attractive targets for identification of undefined Bcc.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of sequencing an orthologous marker gene, such as the 16S rRNA (Lau, Ren, et al, 2007;Lau et al, 2013;Woo et al, 2014;Yuen et al, 2001), recA (Cesarini, Bevivino, Tabacchioni, Chiarini, & Dalmastri, 2009;Costechareyre et al, 2010;Dai, Liu, & Wang, 2012;McDowell, Perry, Lambert, & Patrick, 2008;Owusu-Kwarteng et al, 2012;Payne et al, 2005;Zhu et al, 2013) or groEL (Leclerque & Kleespies, 2008;Woo, Leung, Wong, Ho, & Yuen, 2001) and subsequently determining the phylogenetic position of the isolate in question to achieve identification, speciesspecific gene amplification represents a more intuitive approach that can be applied in the time-critical setting of a clinical laboratory or the rudimentary setting of field work. While the single-nucleotide resolution of gene sequencing methods enables precise phylogenetic placement and discrimination of closely related clones, species-specific gene amplification typing offers a yes or no, unambiguous answer to the identity of an organism .…”
Section: Identification By Species-specific Gene Amplificationmentioning
confidence: 99%